2022
DOI: 10.1111/cgf.14492
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Kinesthetic Garments

Abstract: Figure 1: Given a pose and garment, our method leverages an FEM simulation of the garment (light blue) as it deforms over the body (a) and optimizes the placement of a reinforced material (dark blue) by maximizing energy density for a given area budget. Our algorithm produces a continuous range of designs with various amounts of reinforcement coverage (b,c), allowing designers to explore the trade-off between instrumentation and performance. The selected design is then manufactured using a standard HTV (heat-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Closer to our work, topology optimization has moved into the on-body domain where it has been used for personalized cast design [43] and casts designed for thermal comfort [42]. Most recently, Vechev et al demonstrated the design of kinesthetic garments, which are passively reinforced garments designed to resist a single motion [40]. However, this work only formulates a single compliance minimization objective, and thus cannot be used in a setting that leverages active components.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Closer to our work, topology optimization has moved into the on-body domain where it has been used for personalized cast design [43] and casts designed for thermal comfort [42]. Most recently, Vechev et al demonstrated the design of kinesthetic garments, which are passively reinforced garments designed to resist a single motion [40]. However, this work only formulates a single compliance minimization objective, and thus cannot be used in a setting that leverages active components.…”
Section: Related Workmentioning
confidence: 99%
“…Finding a passive mechanical structure that optimally connects electrostatic clutches placed by the user is a key challenge in the design of active kinesthetic garments. Recent work by Vechev et al [40] demonstrated a method for on-body topology optimization using a single compliance-minimization objective (summarized in Appendix C). Such an objective cannot be applied in our setting, as it has no notion of component states, and the single objective does not sufficiently capture the high-level goal of minimizing motion interference when components are inactive.…”
Section: Automatic Designmentioning
confidence: 99%
See 3 more Smart Citations